Mutual use of trail-following chemical cues by a termite host and its inquiline - Cristaldo, Paulo Fellipe; Desouza, Og; Krasulová, Jana; Jirošová, Anna; Kutalová, Kateřina; Lima, Eraldo Rodrigues; Sobotník, Jan; Sillam-Dussès, David (PloS one, 2014)
Termite nests are often secondarily inhabited by other termite species ( = inquilines) that cohabit with the host. To understand this association, we studied the trail-following behaviour in two Neotropical species, Constrictotermes cyphergaster (Termitidae: Nasutitermitinae) and its obligatory inquiline, Inquilinitermes microcerus (Termitidae: Termitinae). Using behavioural experiments and chemical analyses, we determined that the trail-following pheromone of C. cyphergaster is made of neocembrene and (3Z,6Z,8E)-dodeca-3,6,8-trien-1-ol. Although no specific compound was identified in I. microcerus, workers were able to follow the above compounds in behavioural bioassays. Interestingly, in choice tests, C. cyphergaster prefers conspecific over heterospecific trails while I. microcerus shows the converse behaviour. In no-choice tests with whole body extracts, C. cyphergaster showed no preference for, while I. microcerus clearly avoided heterospecific trails. This seems to agree with the hypothesis that trail-following pheromones may shape the cohabitation of C. cyphergaster and I. microcerus and reinforce the idea that their cohabitation is based on conflict-avoiding strategies.
Keywords: komunikace zvířat; feromony; kooperační chování; výběrové chování; Female; rozšíření zvířat; Isoptera; zvířata; Animal Distribution; polyeny; Choice Behavior; Pheromones; ženské pohlaví; Animal Communication; Cues; Polyenes; podněty; Animals; Cooperative Behavior